Peat humic substances enriched with nutrients for agricultural applications: Competition between nutrients and non-essential metals present in tropical soils - Botero, Wander Gustavo [UNESP]; Oliveira, Luciana Camargo de [UNESP]; Rocha, Julio Cesar [UNESP]; Rosa, Andre Henrique [UNESP]; dos Santos, Ademir [UNESP] (Elsevier, 2010)
Improved agricultural productivity, and reduction of environmental impacts, require studies of the interactions between different soil components. Fertilizers marketed as organic or natural , such as peats or humic substances (HS) extracted from peats, are enriched with macro and micronutrients that, according to the manufacturers, are released to the plant in accordance with its needs. This work investigates the complexation capacity of HS for macro and micronutrient metal species, considering the competition, for HS complexation sites, between non-essential metals (aluminium and lead), present in the soil, and the nutrients. Humic substances were found to possess strong affinities for Pb(II) and Al(III), forming stable complexes, with concomitant release of complexed nutrients. Although HS are already used commercially as organic fertilizers, further studies of methods of HS enrichment, aimed at avoiding losses, are highly desirable from environmental and economic perspectives. © 2009 Elsevier B.V.
Keywords: Agricultural application; Nutrients; Peat humic substances; Toxic metals